Validation and proposal of a short version of the Motivated Strategies for Learning Questionnaire (MSLQ) for Portuguese adolescent students - Morais, Eva; Santos, Anabela Caetano; Mouraz, Ana (Frontiers in Education, 2025)
Self-regulated learning is one of the most relevant learning concepts, representing cognitive, metacognitive, emotional, behavioural and motivational aspects. The Motivated Strategies for Learning Questionnaire (MSLQ) is the most used instrument to measure self-regulated learning. Though, its 81-item structure is lengthy and presents psychometric issues. Additionally, there is no translation/validation of MSLQ for European Portuguese secondary students. This study involved two stages; in the first, the scale’s psychometric properties were examined, and a short version with 56 items was proposed; in the second, the short version was re-analysed. The first sample consisted of 795 adolescents aged 14–19; 429 adolescents formed the second sample, aged 13–17. Confirmatory factor analyses using robust estimators showed a good fit to the data for the three separated first-order models. Also, good reliability values were found, and information reproduction between the original version and this reduced proposal was verified. These results suggest that the proposed Portuguese short version of the MSLQ (MSLQ-PTS) is a valid and reliable measure for adolescent Portuguese samples. Moreover, the shorter version length makes it a more effective tool for practitioners and researchers.